EFFECTS OF WORKLOAD AND JOB STRESS ON EMPLOYEE PERFORMANCE OF BANKING EMPLOYEES: THE MEDIATING ROLE OF JOB SATISFACTION - Ryan Fathurrahman Johan; Aryana Satrya (Jurnal Scientia, 2023)
In the era of banking digitalization, the number of banking employees has decreased from year to year in line with developments in digitalization and the reduced number of bank office networks. Reducing employees in the banking sector will impact employee performance because the number of jobs is disproportionate to the number of existing employees. Employee performance is an important factor in achieving a good level of productivity in a company. Therefore, this study aims to determine the factors that influence the performance of banking employees in Indonesia. Empirical data were collected from 207 conventional bank employees using the online survey method. Analysis method in this study is done by using Structural Equation Modeling (SEM) to test the proposed hypotheses. The results of this study show how workload and job stress negatively affects employee performance, and job satisfaction positively ffects employee performance. The results also found that workload and job stress negatively affects job satisfaction. Furthermore, the results also indicate that job satisfaction mediates the effect of workload and job stress on employee performance. Overall, the results of this study will contribute to the banking sector in preventing job stress experienced by employees to improve employee performance in conventional banks.